2015
DOI: 10.1097/ftd.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Subtherapeutic Posaconazole Exposure and Treatment Outcome in Patients With Invasive Fungal Disease

Abstract: Posaconazole exposure is insufficient in more than 40% of patients at risk of or with invasive fungal disease, and posaconazole exposure is positively correlated with a successful treatment outcome. Therapeutic drug monitoring of posaconazole can detect underexposure and can be helpful in treatment optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…The large number of early levels in this study, however, may help explain the higher proportion of sub-therapeutic levels. When looking at posaconazole levels reported in other studies, the rate of not achieving optimal plasma concentrations varied widely from 20% [ 29 ] to 90% [ 30 ]; however, a majority of the studies report percentages in the range of 20–50% [ 6 , 7 , 21 , 31 34 ]. It can be difficult to compare percentages of therapeutic drug measurements across studies due to the differing therapeutic threshold cut-offs, TDM practices, and patient populations at each site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large number of early levels in this study, however, may help explain the higher proportion of sub-therapeutic levels. When looking at posaconazole levels reported in other studies, the rate of not achieving optimal plasma concentrations varied widely from 20% [ 29 ] to 90% [ 30 ]; however, a majority of the studies report percentages in the range of 20–50% [ 6 , 7 , 21 , 31 34 ]. It can be difficult to compare percentages of therapeutic drug measurements across studies due to the differing therapeutic threshold cut-offs, TDM practices, and patient populations at each site.…”
Section: Discussionmentioning
confidence: 99%
“…For both voriconazole and posaconazole, the relationship between efficacy and drug exposure has been established [ 7 , 10 , 11 ]. A voriconazole plasma level of 1.0–5.5 or 1.0–6.0 μg/ml is generally recommended as the goal range for improved outcomes and minimized toxicities [ 11 , 12 ], and a threshold of >0.5–0.7 μg/ml has been recommended as a therapeutic posaconazole concentration [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…24,30 ; the newer oral delayed release tablet formulation has substantially better, and more reliable, absorption than earlier formulations 39,40 A series of studies have shown a relationship between posaconazole levels and efficacy. 54,57,58 While these studies varied in their rigor with respect to TDM methods and definitions of efficacy, the body of data has led to recommendations of target steady-state trough posaconazole concentrations of > 700 ng/mL for prophylaxis and, provisionally, >1250 ng/mL for treatment of invasive fungal disease. 54,59 In a recent study, Cornely et al found that 90% of adult patients taking the newer delayed release tablets for prophylaxis of fungal infections had steady-state trough levels >700 ng/mL and there was no correlation between drug levels and adverse events.…”
Section: Isavuconazonium Sulfatementioning
confidence: 99%
“…Previous studies on the use of posaconazole in LTx-patients have mostly been conducted with POS-Liq alone, or included only a small subpopulation of LTx-patients. [28][29][30][31] Our study shows that both posaconazole formulations are a safe and effective option for the prophylaxis of IFIs in LTx-patients. With regards to the treatment of IFIs, POS-Tab appears to be the superior formulation.…”
Section: Discussionmentioning
confidence: 62%